THE EFFECTIVENESS OF THE GALLERY WALK TECHNIQUE IN IMPROVING STUDENTS’ SPEAKING SKILLS - Sri Utami Warat; Jusmaniar N; Muhammad Chairil Imran (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
The objective of the research is to find out whether the use of Gallery Walk techniques is effective or not to improve the English students speaking skills of the class XI students at SMA Plus Budi Utomo Makassar. This research uses Classroom Action Research by implementing the Kemmis and MC Taggart design in two cycles. The participants of this research is 28 students class XI at SMA Plus Budi Utomo Makassar in academic year 2024/2025. The research instrument is a speaking test. The Results of this research show that there was a different improvement in the students’ speaking skills in cycle I and cycle II, average score increased. In cycle I, students’ speaking test results the average score was 71.96 included in the fairly good category, and the students test results in cycle II was 81.32 with a good category, means that Gallery Walk technique is effective in improving students speaking skills.